2019 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2019.pr.bumler
|View full text |Cite
|
Sign up to set email alerts
|

How do previous coding experiences influence undergraduate physics students?

Abstract: Electricity and Magnetism Projects and Practices in Physics (EMP-Cubed), a section of introductory, calculus based physics, is designed around problem based learning. Students spend each class working in groups on a single complex physics problem. Some of these problems are computational in nature-students start with code from a visual computer program that runs without accurately accounting for the physics, and they spend the class period applying the physics concepts correctly in the program. Here we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Even then, we found that students who had taken a computer science course still struggled with the syntax and idiosyncrasies of Glowscript. Previous research by Bumler et al [92] found that students with prior computational experiences did not view minimally working programs using the GlowScript platform as authentic computation. The conflict between their previous experiences and the lack of utility of students' previous experiences in the context of this research implies there are difficulties transferring practice to the GlowScript platform.…”
Section: Discussionmentioning
confidence: 97%
“…Even then, we found that students who had taken a computer science course still struggled with the syntax and idiosyncrasies of Glowscript. Previous research by Bumler et al [92] found that students with prior computational experiences did not view minimally working programs using the GlowScript platform as authentic computation. The conflict between their previous experiences and the lack of utility of students' previous experiences in the context of this research implies there are difficulties transferring practice to the GlowScript platform.…”
Section: Discussionmentioning
confidence: 97%